2020
DOI: 10.1177/1971400920937647
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning based detection of intracranial aneurysms on digital subtraction angiography: A feasibility study

Abstract: Background Digital subtraction angiography is the gold standard for detecting and characterising aneurysms. Here, we assess the feasibility of commercial-grade deep learning software for the detection of intracranial aneurysms on whole-brain anteroposterior and lateral 2D digital subtraction angiography images. Material and methods Seven hundred and six digital subtraction angiography images were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The literature review revealed a total number of 21,673 publications. Of all these publications, 13,371 (61.7%) were articles, 2140 (9.9%) were Meeting Abstracts, 1208 (5.6%) were Letters, 965 (4.5%) were Reviews, 716 (3.3%) were Proceedings Papers, and the rest were in the "other publications" category (Editorial Material (3062), Note (388), Correction (93), Book Chapter (55), Early Access (30), News _ Item (29), Reprint (32), Book (1), Discussion (3), Retracted Publication (1), Retraction (1), Bibliography (1)). This study performed the bibliometric analysis of only 13,371 publications that were articles; the other publication types were excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review revealed a total number of 21,673 publications. Of all these publications, 13,371 (61.7%) were articles, 2140 (9.9%) were Meeting Abstracts, 1208 (5.6%) were Letters, 965 (4.5%) were Reviews, 716 (3.3%) were Proceedings Papers, and the rest were in the "other publications" category (Editorial Material (3062), Note (388), Correction (93), Book Chapter (55), Early Access (30), News _ Item (29), Reprint (32), Book (1), Discussion (3), Retracted Publication (1), Retraction (1), Bibliography (1)). This study performed the bibliometric analysis of only 13,371 publications that were articles; the other publication types were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Intracranial aneurysms are the number one cause of non-traumatic subarachnoid hemorrhage. 1 High mortality and morbidity rates of ruptured intracranial aneurysms are still a serious health problem. 2 The survival rate after aneurysmal subarachnoid hemorrhage (SAH) has increased by 17% in the past few decades, probably owing to better diagnosis, early aneurysms repair, prescription of nimodipine, and advanced intensive care support.…”
Section: Introductionmentioning
confidence: 99%
“…Despite broad use of #RadialFirst within cardiology and extensive literature supporting transradial access over transfemoral for percutaneous coronary intervention, the vast majority (>80%) of proceduralists in the United States remain low radial adopters, and many recent studies continue to be exclusively femoral access. 27,28 Nonetheless, this analysis provides useful information about topic trends and discussion within neurointerventional surgery and demonstrates a rise in conversation about the transradial approach.…”
Section: Discussionmentioning
confidence: 98%
“…Both the U-Net model and the 3D CNN network use full convolutional networks for image detection. The introduction of deep learning in the labeling process can improve the detection and diagnosis effect of cerebral hemangioma [ 16 18 ]. CNN can be divided into 2D convolution and 3D convolution according to the dimension of the convolution kernel.…”
Section: Introductionmentioning
confidence: 99%